RF power saving system for smart homes - Martynas Sapurov; Algirdas Baskys; Kazimieras Slivka; Vytautas Bleizgys; Karolis Stasys; Rimantas Simniskis; Valerijus Zlosnikas; Kęstutis Urbonas; Aldas Dervinis; Sarunas Paulikas; Nerijus Paulauskas; Raimondas Pomarnacki; et al. (Heliyon, 2024)
In this work the investigation results of harvesting the RF energy of a 2.4 GHz Wi-Fi signal for supply of smart home leak sensors network are presented. The collected RF energy has been used as an additional source to power the sensors. The main goal of the work was to conduct research on determining the limit values of the RF signal source power and the limit distances between the RF energy harvesting system and the RF signal source, at which it is possible to harvest the RF energy and charge the energy storage capacitor. The PCB-based Yagi-Uda type antenna for RF signal receiving and a suitable RF energy harvesting system was designed for this purpose. The hardware model of the harvesting system was investigated with the designed antenna, as well as with other antennas using a signal generator and Wi-Fi router as a sources of RF signal. The obtained results demonstrate that at typical Wi-Fi router transmitting power, which is 10–17 dBm, RF energy can only be collected when the router is several tens of centimeters away from the harvesting antenna. When a router with a maximum allowed power of 20dBm is used, the distance at which it is possible to collect the RF energy, reaches 120 cm just in the case when both the transmitting and receiving antennas are Yagi-Uda directional antennas.